The effect of supplementary nectar feeders on bird-plant mutualisms in the Cape Fynbos, South Africa - Du Plessis, Monique (Department of Biological Sciences, 2021)
Across the world, people feed birds to interact with nature. A variety of feeder types have been developed over the years to target a broad bird community. Attracting nectarivorous birds to gardens using supplementary nectar feeders is a popular human activity across the globe, but few studies have explored its effects on birds and the plants they pollinate. Nectar feeders may have positive effects, facilitating the urban adaptation of nectarivorous birds, and supplementing their diets when floral resources are scarce. However, supplementary feeders may also lure birds away from indigenous vegetation, affecting the rate of visits to bird-pollinated plants, with consequences for seed set. This study is the first to investigate the effect of nectar feeders on an African plantpollinator mutualism. Given that many plant species in the fynbos biome are bird pollinated, this study was conducted in residential gardens and natural vegetation along the urban edge of the Cape Peninsula, South Africa. I carried out a feeding experiment with a matched paired design to answer two main questions: (1) Do nectar feeders affect bird abundance and distribution ranges? If so, (2) do these affect their visitation rates to bird-pollinated plants? I conducted bird surveys to compare relative bird abundance and local distribution patterns for three feeding guilds (i.e., nectar-specialists, nectar-opportunists and non-nectarivores) between feeder and control treatments (Chapter 2). I then tested whether the presence of nectar feeders in gardens affected sunbird visitation rates to two bird-pollinated Erica species (Erica plukenetii subsp. plukenetii and Erica abietina subsp. atrorosea) in the neighbouring vegetation compared to control sites (Chapter 3). In chapter 2, I found that nectar feeders attracted higher densities of avian nectarivores (but not non-nectarivores) to gardens relative to natural vegetation, and decreased their densities in the neighbouring fynbos, even when floral abundance in the neighbouring vegetation was high. In chapter 3, I found that the consequent changes to sunbird distribution patterns (the main pollinators of ericas) seemed to have no influence on visitation rates to E. abietina, but decreased visitation to E. plukenetii flowers within 300 m of gardens with feeders. Thus, nectar feeders may have positive effects for birds themselves by reducing their urban sensitivity but may also have negative effects on the surrounding fynbos ecosystem. Given that nectar feeders appear to compete with the flowers of E. plukenetii, and perhaps those of other birdpollinated species, supplementary feeding may inadvertently threaten bird-plant pollination networks. This issue is particularly concerning in biomes such as the Cape Floristic Region where many bird-pollinated plants occur near urban edges.